2023
DOI: 10.3390/metabo13050581
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like Peptide-1 Receptor Agonists in Patients with Type 2 Diabetes Mellitus and Nonalcoholic Fatty Liver Disease—Current Background, Hopes, and Perspectives

Abstract: Nonalcoholic fatty liver disease (NAFLD) represents the most common chronic liver disease worldwide, reaching one of the highest prevalences in patients with type 2 diabetes mellitus (T2DM). For now, no specific pharmacologic therapies are approved to prevent or treat NAFLD. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) are currently evaluated as potential candidates for NAFLD treatment in patients with T2DM. Some representatives of this class of antihyperglycemic agents emerged as potentially beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 106 publications
1
1
0
Order By: Relevance
“…A good drug manageability emerged from its negligible effects on heart rate, eGFR, and pancreatic enzymes. Furthermore, the significant reduction in ALT and FLI suggests that oral semaglutide improves liver lipotoxicity due to NAFLD, as previously reported for injectable GLP1-RAs ( 43 ) and, recently, for oral semaglutide as well ( 44 ). The significant change in FLI and not HSI in our study population, which had no signs of NASH (normal liver enzyme levels) at baseline, would reflect the predominant effect of the drug more on waist circumference, which enters the calculation of FLI alone and is more related to visceral fat, than on liver enzymes.…”
Section: Discussionsupporting
confidence: 78%
“…A good drug manageability emerged from its negligible effects on heart rate, eGFR, and pancreatic enzymes. Furthermore, the significant reduction in ALT and FLI suggests that oral semaglutide improves liver lipotoxicity due to NAFLD, as previously reported for injectable GLP1-RAs ( 43 ) and, recently, for oral semaglutide as well ( 44 ). The significant change in FLI and not HSI in our study population, which had no signs of NASH (normal liver enzyme levels) at baseline, would reflect the predominant effect of the drug more on waist circumference, which enters the calculation of FLI alone and is more related to visceral fat, than on liver enzymes.…”
Section: Discussionsupporting
confidence: 78%
“…37 Several studies have investigated the hepatoprotective effects of GLP-1RAs in patients with type 2 diabetes. 39 Gameil et al 40 reported that the addition of liraglutide or dulaglutide to existing therapies was associated with significant improvements in FIB-4 and metabolic parameters in patients with concomitant type 2 diabetes and NAFLD.…”
Section: Discussionmentioning
confidence: 99%